Implementasi Clean Architecture pada Aplikasi Android Rinjani Visitor - I Dewa Agung Adhinata Budhiastawa; Dwi Ratnasari; Noor Alamsyah; Andy Hidayat Jatmika; Raphael Bianco Huwae; M. Taqwa Mahajaya (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2026)
The growing complexity of mobile applications necessitates scalable architectural solutions to streamline maintenance and feature expansion. This study presents the implementation of Clean Architecture in the Rinjani Visitor Android application, an ecotourism platform for Mount Rinjani National Park, Indonesia. The application integrates local tourism services while addressing challenges in code maintainability. Leveraging Flutter and Dart, the architecture is structured into three decoupled layers (presentation, domain, and data) to isolate business logic from technical implementation. The methodology encompasses requirement analysis, feature-based code structuring, and user acceptance testing via black-box methods. Results demonstrate successful layer integration, with all 21 tested functionalities adhering to specifications. The modular design simplifies collaborative development, reduces code interdependency, and supports agile enhancements. The study advocates periodic architectural reviews to sustain these benefits amid evolving technological demands.